Sn(OTf)2-Catalyzed Allylic Substitution of Thiols to Allyl Alcohols: Access to Allyl Sulfides - Chen, Yibo; Gao, Zhenbo (Synthesis, 2022)
A novel method for the mild and efficient synthesis of allyl sulfides has been developed with allyl alcohols and thiols as substrates. The desired allyl sulfide was obtained using a catalytic amount of Sn(OTf)2 in dichloromethane at room temperature after a reaction time of 12 hours. A diverse range of allyl sulfides have been obtained with good to excellent yields, including both linear and cyclic derivatives (27 products). Additionally, gram-scale reactions can be easily carried out with only 1 mol% catalyst, giving over 90% yields, which further proves the efficiency of our approach in synthesis. This methodology has both deep research significance and application value, providing a new pathway to access sulfide compounds. We strongly believe our method would be attractive to synthetic chemists and would be widely used in synthetic chemistry.
Keywords: allyl alcohols; allyl sulfides; allylic substitution; C–S bond formation; thiols